2010
DOI: 10.1149/1.3485241
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Atomic Layer Deposition for Epitaxial Oxides on Silicon

Abstract: Thin films of crystalline oxides integrated with silicon are of interest for novel devices that utilize the rich variety of functional properties of oxide materials. Growth of crystalline oxides on silicon requires careful control of a nanometer thin transition region to avoid deleterious side reactions such as oxidation of the substrate. Submonolayer surface reconstructions of alkaline earth metals such as Sr are key to controlling the interface for successful growth. Previously, this has only been accompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The silicate layers at the MgO=SiO 2 and SrO=SiO 2 interfaces are about twice as thick as that of the Al 2 O 3 =SiO 2 interface. This result agrees well with the experimental results of other studies, wherein MgO and SrO are reported to form a silicate layer at the interface with SiO 2 , 30,31) whereas the silicate layer is barely formed at the Al 2 O 3 =SiO 2 interface. 32,33) In order to clarify the ion species that contributes most to the electric dipole, we calculated the charge migration moment (CMM) for each species.…”
Section: Sisupporting
confidence: 93%
“…The silicate layers at the MgO=SiO 2 and SrO=SiO 2 interfaces are about twice as thick as that of the Al 2 O 3 =SiO 2 interface. This result agrees well with the experimental results of other studies, wherein MgO and SrO are reported to form a silicate layer at the interface with SiO 2 , 30,31) whereas the silicate layer is barely formed at the Al 2 O 3 =SiO 2 interface. 32,33) In order to clarify the ion species that contributes most to the electric dipole, we calculated the charge migration moment (CMM) for each species.…”
Section: Sisupporting
confidence: 93%
“…In these cases, the dipole layer is induced by the migration of metal cations (Mg + , Sr + ) from the high-k oxide side to the SiO 2 side, and a silicate layer is formed at these interfaces. The silicate-layer formation has been observed experimentally at MgO=SiO 2 and SrO= SiO 2 interfaces 20,21) but not at Al 2 O 3 =SiO 2 interfaces. 22,23) These results indicate that the negative V FB shift is induced in the course of the formation of stable silicate phases.…”
mentioning
confidence: 97%
“…The silicate layer is the compositional transition layer at the interface, which is defined as the interval between the point at which the Si density becomes 90% of the bulk SiO 2 , and the point at which the density of the high-k metal ion becomes 90% of the bulk value. The silicate layers at the MgO/SiO In the previous experimental studies, MgO and SrO are reported to form a silicate layer at the interface with SiO 2 , [26,27], whereas the silicate layer is barely formed at the Al 2 O 3 /SiO 2 interface. [28,29]…”
Section: Simulation Resultsmentioning
confidence: 94%